Study on The Quality of Environmental Impact Assessment Documents Evaluated by EIA Assessment Commission of South Sumatra Province for Preventing Environmental Degradation - Rian Syafni; Dedik Budidanta; Moh Rasyid Ridho (Sriwijaya Journal of Environment, 2021)
The quality Environmental Impact Analysis (EIA) document does not absolutely guarantee effectiveness of EIA implementation, but it can be the main basis in environmental management and monitoring. So it is very necessary to evaluate the quality of the EIA Document. This research aims to evaluate the quality of the EIA document assessed by the South Sumatra Province EIA Assessment Commission and appraise the compliance of the person in charge of the business and/or activity in implementing the EIA Document. The research method used is descriptive qualitative. The sample is taken using total sampling technique (12 EIA Documents that have been assessed between 2018-2020 and already have an Environmental Feasibility).  The result of the consistency test showed that  42% is very good, 50 % is good and 8% is bad. All the EIA Documents own very good necessity aspect. The results of the relevance test showed that 58% is very good and 42% is  good. Based on the follow-up test of the EIA document, there are 16.7% of the evaluated documents implemented since 2019 and 8% of the documents have been implemented since 2020, but has not complied with the fulfillment of the obligations contained in the Environmental Permit.